Frontiers of space exploration - Launius, Roger D. (Greenwood Press, 2004)
Chronicles space exploration's history, discussing such topics as the race to the moon and the advent of the Space Shuttle and Skylab, and includes biographies of astronauts, scientists, and others related to space exploration; primary documents; a table of American space flights; and an annotated bibliography.